1998
DOI: 10.1017/s0013091500019416
|View full text |Cite
|
Sign up to set email alerts
|

Radial functions on compact support

Abstract: In this paper, radial basis functions that are compactly supported and give rise to positive definite interpolation matrices for scattered data are discussed. They are related to the well-known thin plate spline radial functions which are highly useful in applications for gridfree approximation methods. Also, encouraging approximation results for the compactly supported radial functions are shown.1991 Mathematics subject classification: 41A05, 41A25, 41A63, 42A82, 65D05, 65D07.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Several remedies to circumvent the problem were proposed. They are, in particular, domain decomposition approach [27], preconditioning and compactly supported RBF [6,26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Several remedies to circumvent the problem were proposed. They are, in particular, domain decomposition approach [27], preconditioning and compactly supported RBF [6,26,29].…”
Section: Introductionmentioning
confidence: 99%
“…In BPNNs a common barrier is the training speed (i.e., the training speed increases as the number of layers, and number of neurons in a layer grow) [3]. To circumvent this problem a new paradigm of simpler neural network architectures with only one hidden layer has been penetrated to many application areas with a name of Radial Basis Function Neural Networks (RBFNs) [4,[6][7][8][9][10][11][12][13][14]. RBFNs were rst introduced by Powell [15][16][17][18] to solve the interpolation problem in a multi-dimensional space requiring as many centers as data points.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution of this problem, Wendland (see [18]) constructed functions φ d,ℓ = p d,ℓ χ [0,1] , for integers d ≥ 1 and ℓ ≥ 0, such that φ d,ℓ • ρ d has a nonnegative Fourier transform and belongs to C 2ℓ (R d ), the degree of the polynomial p d,ℓ being minimal. Other noteworthy constructions are those of Buhmann [4], who constructed "single-piece" piecewise functions of the form φ • ρ d , where φ = qχ [0,1] with q analytic on (0, 1], as well as several families constructed by Gneiting (see [8] and the references therein). Recently, Al-Rashdan and the author (see [2]) showed that the B-spline ψ k , having simple knots at {±1, ±2, .…”
Section: Introductionmentioning
confidence: 99%
“…The function η 4,3 = Dη 3 has regularity (4,3,0) and the first piece of η 4,3 equals 1 5 (−b 12 + (5 − 2b 14 )t 2 + 20t 2 log t). It follows that η 4,3 ∈ U 2 and therefore, by Theorem 7.4, η 4,3 has regularity (2, 2, 1).…”
mentioning
confidence: 99%